Ritual as lived ethics: A phenomenological study of symbolic meaning in Javanese Water Ritual - Murdianti, Rena; Subiyantoro, Slamet (Universitas Muhammadiyah Malang, 2026)
Phenomenological ritual studies tend to prioritize symbolic interpretation over participants' lived experience. This research explores: How do Dawuhan ritual participants experience symbolic elements as ethical formation? Through in-depth interviews with 12 participants and three-month participant observation in Gangging Hamlet, Sidomulyo Village, this study employs Husserlian phenomenological reduction and Schutzian thematic analysis to identify structures of collective consciousness. Three key themes emerged: first, water is understood not as abstract symbol but as lived experience of ecological reciprocity generating moral responsibility; second, communal eating functions as embodied solidarity through somatic and emotional engagement; third, while core values are widely shared, tensions emerged around spiritual authority and offering interpretations, revealing ritual ethics as ongoing intersubjective negotiation rather than static consensus. These findings extend Schutz's lifeworld theory by demonstrating ethical values emerge through embodied ritual practice rather than cognitive interpretation alone. Methodologically, this study operationalizes epoché and bracketing in ritual studies, capturing lived ambiguity beyond symbolic coherence. This provides the first phenomenological account of Javanese water rituals centering participant voice, revealing previously undocumented ethical contestations within communal harmony. The research contributes empirically by documenting how individual phenomenological encounters converge into collective ecological consciousness while maintaining interpretive plurality. Limitations include reliance on participant narratives and potential researcher interpretation bias. Studi fenomenologi ritual cenderung memprioritaskan interpretasi simbolik di atas pengalaman hidup partisipan. Penelitian ini mengeksplorasi pertanyaan: Bagaimana partisipan ritual Dawuhan mengalami elemen simbolik sebagai pembentukan nilai etis? Melalui wawancara mendalam dengan 12 partisipan dan observasi partisipan selama tiga bulan di Dusun Gangging, Desa Sidomulyo, penelitian ini menggunakan reduksi fenomenologis Husserl dan analisis tematik Schutzian untuk mengidentifikasi struktur kesadaran kolektif masyarakat. Tiga tema kunci muncul: pertama, air dipahami bukan sebagai simbol abstrak melainkan sebagai pengalaman hidup tentang timbal balik ekologis yang menghasilkan tanggung jawab moral; kedua, makan bersama berfungsi sebagai solidaritas yang diwujudkan melalui keterlibatan somatik dan emosional; ketiga, meskipun nilai-nilai inti dibagikan secara luas, ketegangan muncul seputar otoritas spiritual dan interpretasi sesaji, mengungkapkan bahwa etika ritual bukanlah konsensus statis tetapi negosiasi intersubjektif yang berkelanjutan. Temuan ini memperluas teori lifeworld Schutz dengan menunjukkan bahwa nilai-nilai etis muncul melalui praktik ritual yang diwujudkan daripada interpretasi kognitif semata. Secara metodologis, penelitian ini mengoperasionalkan epoché dan bracketing dalam studi ritual, menangkap ambiguitas yang hidup di luar koherensi simbolik. Keterbatasan mencakup ketergantungan pada narasi partisipan dan potensi bias interpretasi peneliti.